Upfront Simulations and (Their) Democratization – Where We Are? - Čelik, Anže (International Conference Fluid Power 2025: Conference Proceedings, 2025)
Upfront simulation involves activities in the early design phase. The goal is to identify potential problems early, optimize designs, and predict performance when changes are cheaper and easier to implement. Democratization of simulation is understood as making simulation tools accessible to non-simulation experts within a company, organization, or community. This means removing barriers that limit product managers, designers, or even non-experts from running simulations and making decisions. The paper presents current status regarding upfront simulations and their democratization within company Poclain. The practical cases demonstrate the abilities brought through the upfront (or front-loading) simulations. It is also explained what activities have been made to democratize (deploy) simulation tools among the group of design engineers. The power of upfront simulations is also demonstrated on real case example, performed in real time (in-situ) at the conference. It emphasizes its ease of use, the importance of understanding the product behavior as well as the gain in time to market.